Argentina's countercyclical credit policy response: macroprudential regulation and public bank credit during Covid-19 - Schclarek Curutchet, Alfredo (2021)
Fil: Schclarek Curutchet, Alfredo. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.